MAIN TRENDS OF MAIZE BREEDING IN ARRIGC NAMED AFTER I.G. KALINENKO - G. Ya. Krivosheev; A. S. Ignatiev; N. А. Shevchenko (Зерновое хозяйство России, 2018)
The main trends of the breeding of new corn hybrids in ARRIGC are the breeding of the hybrids with tolerance to drought, high water yielding capacity of the grain during ripening, high contents of starch in grain, breeding for ensilage and green forage. For each trend of the breeding process there was developed and introduced such new initial material as self-pollinated lines and populations. The new drought tolerant lines ‘КV 498’, ‘КS 311’, ‘Zp 498А’, ‘DK 655’ and others have been created possessing little residual water deficit (7.9 – 9.2 %) during flowering and its slight increase (up to 9.3 – 10.1 %) in the phase of milky-wax ripeness when the drought becomes stronger. They have been included into the program of hybridization on the breeding of drought tolerant corn hybrids. The new self-pollinated lines ‘ZS 226’, ‘ZS 123’, ‘ZS 121’, ‘КV 263’, ‘ZS 244’ with intensive drying of grain (more than 1% per day) while maturing have been developed for the breeding of the corn hybrids with a low harvesting moisture content of grain. The initial material ‘Assiniboine’, ‘Pima indians’, ‘Dalnevostochnaya mestnaya’, ‘Kanadskaya mestnaya’, etc. with 69.0 – 72.8 % starch in grain was introduced for the breeding of corn hybrids of the kind of Zea mays amylaceae with a high contents of starch in grain. The self-pollinated generations I2 of the subspecies Zea mays ceratina ‘57/1’, ‘55/1’, ‘197/1’, ‘170/1’, ‘188/1’, ‘20/5’ with 69.2 – 70.3 % of amylopectin starch in grain have been developed. The tall, well-leafy self-pollinated lines ‘КV 399’, ‘КV 469’, ‘КV 272’ have been chosen for the breeding on ensilage and green forage. Due to the use of the new initial material there have been selected drought tolerant corn hybrids. They are ‘Zernogradsky 282 MV’, ‘Zernogradsky 288 MV’, ‘Zernogradsky 354 MV’ with a high contents of starch, rapidly drying ‘Zernogradsky 242 MV’ and ‘Zernogradsky 404 AMV’ for silage.